Fractional Spin and Josephson Effect in Time-Reversal-Invariant Topological Superconductors - Camjayi, Alberto (2017)
Time-reversal-invariant topological superconducting (TRITOPS) wires are known to host a fractional spin /4 at their ends. We investigate how this fractional spin affects the Josephson current in a TRITOPS-quantum dot-TRITOPS Josephson junction, describing the wire in a model that can be tuned between a topological and a nontopological phase. We compute the equilibrium Josephson current of the full model by continuous-time Monte Carlo simulations and interpret the results within an effective low-energy theory. We show that in the topological phase, the 0-to-π transition is quenched via formation of a spin singlet from the quantum-dot spin and the fractional spins associated with the two adjacent topological superconductors.